Implementasi Flutter Framework & Metodologi Lean UX Kanban Dalam Aplikasi Reservasi The Bbalbong - Tiawan Tiawan; Nopi Rahmawati (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
In this millennial era, people are very happy to be able to get food at the restaurant of choice, therefore the number of visitors to the restaurant has increased rapidly, especially during meal times and holidays, many customers are disappointed because they cannot get a place at their favorite restaurant, this will affect the rating of the restaurant and also in the restaurant service process, several problems arise such as customers who wait too long for food menus, and lack of information on the availability of menus. Based on the problems, we make an application for customers can reserve a place and food as a solution. The Applications made using the dart programming language with a flutter framework and the Lean UX KANBAN methodology so that the application is more effective and efficient and focuses on the division of tasks in groups. Flutter Framework is a product from Google that is suitable for application developers who have a focus on UI and UX design, for the methodology used, namely Lean UX Kanban, with the LEAN UX methodology can measure success so that the design and development of system products can be effective in a short time, Kanban methodology also helps in the division of team tasks and prioritizes to be able to speed up the application creation process.